Developing Science Literacy Skills at MASS Khoiriyah Hasyim Seblak through Training on the Use of Integrated STEM Student Worksheets - Rochim, Roudhoutul Aulia; Af’idah, Noer; Rokhmah Wati, Dian Anisa; Mughiroh, Ainun Fitri; Yuni K, Kusnul Ciptanila; Dwinata, Anggara; Falah, Fajrul; Wulandari, Desi (Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
Science literacy skills are of paramount importance for students. Preliminary findings indicate that the average level of science literacy skills remains comparatively low. The utilization of integrated science worksheets is regarded as a potential solution. However, research on the impact of integrated STEM worksheets on training science literacy skills remains limited. Therefore, the objective of this study is to develop a training program to enhance science literacy skills through the implementation of integrated STEM worksheets. This study delineates the results of the science literacy skills test. The activity encompassed 30 students, who participated in a series of training sessions encompassing preparation, implementation, and evaluation. The findings indicated an enhancement in the students's science literacy test scores, with 100% of the students attaining the mastery criteria following the implementation of the integrated STEM worksheets. The present study demonstrates that the implementation of integrated STEM worksheets can enhance students' science literacy skills